POTENTIAL INHIBITION OF AKT1 AND P53 PROTEIN IN COLON CANCER BY GALLIC ACID DERIVATIVES COMPOUND WITH MOLECULAR DOCKING APPROACH - Humaedi, Aji; Kurniawan, Muhammad Rizki; Halimatushadyah, Ernie (Universitas Muhammadiyah Magelang, 2024)
Colon cancer is a degenerative disease that attacks the large intestine through a process of initiation, promotion and progression. Related research reports that overexpression of the AKT1 protein was found to be 60-70% and p53 at 50%. This research analyses the affinity, stability and interaction of gallic acid derivative compounds and reference ligands with the target proteins AKT1 and p53 by molecular docking. The study stages carried out include preparation and optimisation of target proteins and ligand compounds, file creation and simulation processes, and analysis and visualisation of docking results. The docking simulation results show that four gallic acid derivative compounds provide potential inhibitory activity against the AKT1 and p53 proteins based on binding energy values. BG and 2HBG compounds have strong inhibitory power against target proteins, thus enabling the formation of strong interactions and complexity towards the active site of amino acids with a bond distance of <3.0 Å. Thus, gallic acid derivative compounds have potential as inhibitors and are expected to activate other proteins, causing cancer cell apoptosis.